MENELUSURI SEJARAH DAN KEBUDAYAAN BULELENG MELALUI TINGGALAN ARKEOLOGI - I Kadek Edi Palguna; I Komang Sukayasa (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The archaeological relationship with the community is very important, both in its management and utilization so that later it can be mutually beneficial. The existence of archaeological remains scattered in the Buleleng area indicates that long before there was a high civilization, thus on this occasion there will be a way of history and culture of Buleleng based on the existing archaeological remains. In this study there are several stages, namely data collection through observation and literature study, data processing with classification, data analysis with qualitative methods, and description of research results. The results of the study show that there are many archaeological remains scattered in the Buleleng area, the findings of the perimbas ax are the opening evidence of human life who inhabited Buleleng since the Pleistocene period. Along with the development of the human mindset, the activities of human life became increasingly complex, starting to recognize the belief system, social organization and government system controlled by the king until the entry of colonial influence in Buleleng. The variety of Buleleng culture in the past was very complex, starting to develop, arts, agricultural knowledge systems, languages, shipping and foreign cultural influences.Keywords: History, Culture, Archaeological remains